Improvement of hydrogenated amorphous silicon germanium thin film solar cells by different p-type contact layer. (January 2016) - Cho, Jaehyun; Pham, Duy Phong; Jung, Junhee; Shin, Chonghoon; Park, Jinjoo; Kim, Sangho; Tuan Le, Anh Huy; Park, Hyeongsik; Iftiquar, S.M.; Yi, Junsin
Abstract: In this study, we report an appreciably increased efficiency from 6% up to 9.1% of hydrogenated amorphous silicon germanium (a-SiGe:H) thin film solar cells by using a combination of different p-doped window layers, such as boron doped hydrogenated amorphous silicon (p-a-Si:H), amorphous silicon oxide (p-a-SiO x :H), microcrystalline silicon (p-µc-Si:H), and microcrystalline silicon oxide (p-µc-SiO x :H). Optoelectronic properties and the role of these p-layers in the enhancement of a-SiGe:H cell efficiency were also examined and discussed. An improvement of 1.62 mA/cm 2 in the short-circuit current density ( J sc ) is attributed to the higher band gap of p-type silicon oxide layers. In addition, an increase in open-circuit voltage ( V oc ) by 150 mV and fill factor (FF) by 6.93% is ascribed to significantly improved front TCO/p-layer interface contact.